Acquiring initial American Board of Radiology certification in the United States - Mills, Michael D. (Quantitative Imaging in Medicine and Surgery; Vol 4, No 6 (December 02, 2014): Quantitative Imaging in Medicine and Surgery, 2014)
The American Board of Radiology (ABR) is one of 24 independent national boards that are members of the American Board of Medical Specialties (ABMS). It was founded in 1934 to certify physicians in Radiology, and later in other various specialties and sub-specialties related to radiology. It is a not-for-profit organization, and its only purpose is the certification of medical professionals. In 1948, it began the certification of medical physicists. It is unusual for non-physicians to be certified by a national board that is a member of the ABMS. The ABR is currently the only national board in the US that certifies medical physicists. You can see some of the details for initial certification at this site: http://www.theabr.org/ic-rp-landing.